Paraguay report on deforestation 2000-2024 - Elverdin, Pablo; Illescas, Nelson (International Food Policy Research Institute, 2025)
The definition of “forest” varies between countries, and while the differences may be marked by small subtleties, this can imply important divergences in what is understood by deforestation and/or forest degradation. A first approximation to the definition of forests in Paraguay arises from Art. 5 of Law 2524/04, on “zero deforestation” in the Eastern Region.1 There, “native forest” is defined as any native or autochthonous ecosystem, whether or not intervened, regenerated by natural succession or other forestry techniques, which occupies a minimum area of two hectares, characterized by the presence of mature trees of different ages, species and varied size, with one or more canopies that cover more than 50% (fifty percent) of that area and where there are more than sixty trees per hectare of fifteen or more centimeters in diameter measured at breast height.